Evaluation of Nurses’ Practices Concerning Isolation Techniques for Adult Leukemic Patients in Baghdad Teaching Hospitals - Ali Dukhan (Iraqi National Journal of Nursing Specialties, 2023)
Objective: To evaluate nurses’ practices concerning isolation techniques for Adult Leukemic Patients (ALP). Methodology: A descriptive study was carried out at the isolation rooms at leukemic wards in Baghdad Teaching Hospitals, starting from Jan. 27th 2008 up to the 27th of Apr. 2008. To achieve the objectives of study, a non-probability "purposive" sample of (50) nurse was selected out of four Teaching Hospitals in Baghdad city were selected according to the criteria of the study sample. The study instrument consisted of two major parts. It is based on the review of literature. First is concerned with demographic data for nurses; and the second part is observational tool (checklist) is composed of (83) item. The content validity of the instrument was established through a panel of (12) experts. Reliability of the study scale was determined by the researcher and co-observe reliability was performed for determination of the checklist, pearson correlation coefficient was computed for each determination. The results indicated that the correlation coefficient was م 0.82 at the level (p 0.05) which was statistically acceptable. Data were collected through the use of the observational tool, which was analyzed through the use of two statistical approaches; descriptive statistical analysis (frequencies, percentage, standard deviation, range of scores, mean of scores and relative sufficiency) and inferential statistical analysis (correlation coefficient). Results: The findings of study revealed that the evaluation of nurses’ practices found (28.2%) was out of comparison relative sufficiency, (27.2%) was low relative sufficiency, (31.1%) was moderate relative sufficiency, and (13.6%) was high relative sufficiency what means that most of the nurses’ practices is of moderate scores. Recommendations: According to the results of this study, the researcher recommends to develop an assessment sheet for skill and daily note in the leukemic wards for isolation rooms of adult leukemic patients, the education level should be improved, a special training program should be given for the nurses working in leukemic wards.